New Methodologies and Techniques for a Sustainable Organic Chemistry - Mordini, Alessandro (Springer, 2017)
Chemical industries have to face the big challenge of finding adequate processes to produce large quantities of new products for which there is a present need, decreasing at the same time both the impact on the environment and the risk of disasters. These issues have led to the establishment of new concepts of sustainable development as affirmed in the Rio Declaration on Environment and Development in the early 90’s and has been the subject of intensive studies in the last two decades. The book addresses this challenge collecting the recent “New Methodologies and Techniques for a Sustainable Organic Chemistry”.